Reinforced high strength concrete beams under shear - Lim, Darren Tze Yang (2019)
This thesis presents a discussion on the shear behaviour of reinforced high strength concrete beams and new proposed methods to predict the shear strength of reinforced normal and high strength concrete beams. High strength concrete is an advanced construction material with increased tensile strength and modulus of elasticity compared to normal strength concrete. Concrete structural elements with higher tensile strength for concrete material could delay the formation of the first crack and increase the cracking load.